(3CSS GdYdGbGJ GdGbJUGOjI GdOhdjIs - (3eLOj eMehO(B, (3TgGHs; (3ShRj(B, (3YOdj fGTOs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2010)
(3eGgjI heXGgQ GdYdGbGJ GdEbJUGOjI GdOhdjI heOi JejRgG Yf YdGbGJ GdEbJUGOGdOGNdj,GdedGeM hGdNUGFU GdeMOOI dWHjYI GdEbJUGO GdYGdej habG ddJWhQGJ GdWGQFI Ydi GdYdGbGJ GdEbJUGOjI GdOhdjI,GdfXQjGJ GdeaSQI ddJHGOd GdOhdj, GdYdGbGJ GdfbOjI hGdeGdjI GdOhdjI,GdSjGSGJ GdJLGQjI,GdfXGe GdLOjO ddJLGQI GdOhdjIs
Keywords: (3GdGbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdYdGbGJ GdEbJUGOjI GdOhdjIs